Analisis Profitabilitas pada Proyek Rehabilitasi Jalan Banjaragung Pulosari Jombang - Dita Irtanti Febrianita; Totok Yulianto; Meriana Wahyu Nugroho; Titin Sundari (Jurnal Sipil Terapan, 2024)
Profitability analysis is a key factor in evaluating the success of construction projects. This study focuses on the profitability of the Banjaragung - Pulosari road rehabilitation project in Jombang. The rehabilitation project spans 1,566 meters in length and 3 meters in width, with a project value of IDR 1,534,120,251. To determine the profit level, a profitability analysis is required. The main objective of this report is to provide an understanding of profitability analysis in the construction industry, particularly in the Banjaragung - Pulosari road rehabilitation project in Jombang, by presenting the Return on Investment (ROI), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR) methods as tools for evaluating profitability. The analysis results show a favorable outcome with an ROI of 29% and an IRR of 10.42% per year, which is higher than the East Java Regional Development Bank’s Prime Lending Rate (SBDK) of 6% per year. A BCR of 1.0669 also indicates that the benefits exceed the costs, signifying that the project has high investment return potential and is viable to undertake.